(untitled) (Journal of Asian Development Studies, 2019)
This study is an attempt to investigate the impact of gross fixed capital formation (GFCF), trade openness and wage proxy on employment in Pakistan. Annual data series is used from the period 1977 to 2010. Unit root test is used to check the properties of time series data. Johansen co-integration technique was applied to determine long run relationship. The empirical findings suggest that there are two co-integrating vectors during the concerned period of time in Pakistan. The study found a positive relationship of employment with GFCF and trade openness and negative with wage proxy. The value of ECM (-0.109558) also shows a significant speed of adjustment.